SIFAT FISIK, SIFAT ORGANOLEPTIK DAN AKTIVITAS ANTIOKSIDAN SUSU BUBUK KEDELAI HITAM BERDASARKAN KONSENTRASI TWEEN 80 - Riska Ciptasari; Nurrahman Nurrahman (Jurnal Pangan dan Gizi, 2020)
Soy milk is one alternative to cow's milk for lactusa intolerance patients. The utilization of black soy less is attention and not as popular as yellow soybean because of the color that is less interesting. Another alternative in the processing of milk is the manufacture of milk powder. Processing of instant soy milk powder using foam-mat drying method required addition of filler material ie maltodextrin and Tween 80. With the addition of proper Tween 80 concentration expected to produce more stable milk powder. The general purpose of this research is to know the effect of Tween 80 concentration variation on physical properties, organoleptic properties and antioxidant activity of black soybean milk powder. Experimental method of experimental type using Completely Randomized Design (RAL) monofactor with Factor addition of Tween 80 concentration (0, 0,25, 0,5, 0,75 and 1 percent). The product analyzed physical properties (water absorption, moisture content, solubility and settling rate), organoleptic properties and antioxidant activity. The best result of antioxidant activity was 33,70% RSA at concentration 0,25%, water absorption 2,77 ml / g at concentration 0,25%, water content, 8,98% at concentration 0,25%, solubility 84,435% at a concentration of 0.75% and a precipitation rate of 10 s at a concentration of 0.25%. While the best organoleptic test is at concentration 0.25%. The conclusions of the research on black soybean milk powder with the addition of Tween 80 concentration showed a real difference for each test conducted where black soybean milk powder with the addition of Tween 80 0.25% concentration was the best treatment.